Robust Light‐Emitting Devices: Laser‐Like Emission from a Sandwiched MoTe2 Heterostructure on a Silicon Single‐Mode Resonator (Advanced Optical Materials 20/2019). Issue 20 (21st October 2019) - Fang, Hanlin; Liu, Jin; Lin, Qiaoling; Su, Rongbin; Wei, Yuming; Krauss, Thomas F.; Li, Juntao; Wang, Yue; Wang, Xuehua
Abstract : 2D materials‐based nano light sources have been developed for silicon photonics. In article number 1900538, Juntao Li, Yue Wang and co‐workers report the room temperature laser‐like emission from a sandwiched MoTe2 heterostructure on a silicon single mode resonator at 1319 nm. The authors observe much better environmental stability and demonstrate single‐mode operation with a wide free spectral range. These results lend further support to the paradigm of 2D materials‐based integrated light sources on a silicon platform.